An improved bone transport surgical method for treating chronic ischemic ulcers (thromboangiitis obliterans) - Zhao, Liang; Lei, Yu; Pang, Mengru; Wei, Zairong (Frontiers in Surgery, 2022)
Introduction：The chronic ischemic injury of the upper/lower limbs caused by thromboangiitis obliterans (TAO, Buerger’s disease) is difficult to heal, leading to high morbidity and amputation risk, seriously lowering the quality of life of patients. So far, the pathogenesis of this disease is still not clear, and there are still no effective therapeutic approaches. Here we first use improved bone transport technique to treat TAO-related foot ulcers and have achieved good therapeutic effects. Materials and Methods: In this report, there are 22 patients meet the inclusion criteria and we provide an improved bone transport technique to repair thromboangiitis obliterans (TAO, Buerger’s disease) related lower limbs chronic wounds, which have minimally surgical incision and satisfying surgical field. Results: The improved bone transport technique resulted in TAO-related chronic lower extremity wound healing in most patients (18, M: F 16:2) within the first treatment cycle. All wounds healed completely after two treatment cycles. After two treatment cycles, the patient's foot cold sensation was significantly relieved, and the rest pain in the lower extremities was significantly relieved (VAS, P<0.0001). Furthermore, the Laser Doppler flowmeter showed that the blood perfusion and percutaneous oxygen pressure of the affected foot were higher than in preoperation (P<0.0001). To conclude bone transport technology is available for the refractory wounds of the extremity, which may promote healing by increasing blood circulation and tissue oxygen supply. Conclusions: In summary, the improved surgical method of bone transport technique is worth considering in the treatment of thromboangiitis obliterans related foot ulcers.